The last of the husbandmen : a novel of farming life - Logsdon, Gene (Ohio University Press, 2008)
"Nan turned to see Ben's faceturn as hard and white as asauerkraut crock. When he didnot respond, Nan figured thathe was just going to back offas he usually did, the shy andretiring husbandman. She didnot know her history. She didnot know that shy and retiringhusbandmen have been knownto revolt against oppressionwith pitchforks drawn."--The Last of the Husbandmen In The Last of the Husbandmen, Gene Logsdon looks to his own roots in Ohio farming life to depict the personal triumphs and tragedies, clashes and compromises, and abiding human character of American farmingfamilies and communities.